Belajar dari Kasus RS Sumber Waras Ketika Kecakapan Profesional Auditor Offside - Sopian Sopian (AKRUAL: JURNAL AKUNTANSI, 2017)
AbstractInvestigative audit or forensic accounting can be used to detect a fraud, specially corruption. For that reason, investigatif auditors or forensic accountants are required to perform profesionally the standards of audit in every assigment. With descriptive normative reseach method, it is highly recomendated that Investigative Audit separated from the The Audit of Special Purposes since it has the objectives to search and gather facts and evidences and prohibited to promote opinions. When the auditors claim that they are familiar with the law, the fact that they less competence in law, the auditors opinion is misleading.